The relationship between fixed orthodontic treatment and tooth discoloration: Hubungan perawatan ortodonti cekat dengan diskolorisasi gigi - Habar, Eddy Heriyanto; Prihastuti, Yuli (Makassar Dental Journal, 2025)
The use of fixed orthodontic appliances can cause side effects, one of which is tooth discolouration, which can affect patient com-fort and confidence. This study examines the relationship between fixed orthodontic treatment and the degree of tooth discolora-tion. Descriptive analytical study with a cross-sectional approach using 24 subjects; 12 users and 12 non-users of fixed orthodon-dontic appliances. After Spearman correlation test, it was found that the mean discolouration score in users of fixed orthodontic appliances was 1.25, while non-users was 0.5. There was a significant relationship between the use of fixed orthodontic ap-pliances and tooth discolouration (r=0.63; p=0.001), indicating a strong correlation. It is concluded that there is a significant and strong relationship between the use of fixed orthodontic treatment and the level of tooth discolouration.